Assessment of Health Protective Behaviors among Patient with Thalassemia at the Women's and Children’s Hospital in Al-Muthanna City - Radha M. Lefta (Journal of Global Pharma Technology, 2018)
Background: Thalassemia is one of the most common disorders in the world, mostly in the region located around and nearby the Mediterranean Sea. People who are under 30 are most likely to have this disease and that's because of short life expectancy for thalassemia patients, due to life threatening complications and possibly the lack of health protective. Objectives: The study aimed to identify the health Protective behaviors through utilization (Nutrition, Drug, follow up, and Socio-Psychology) domains and to determine correlation between overall health protective behaviors and demographics data. Methodology: The study design a quantitative research by a descriptive study, the sampling it is non-Probability